THE IDIOMATIC PHRASES AND ITS ORAL LANGUAGE TYPOLOGY (Andamios, Revista de Investigación Social, 2004)
A former investigation about the oral “idioms” typology. They are seen as cultural texts with specific uses and a peculiar memory and ideology functionning.